Fruit Damage Patterns Caused by Ovipositing Females of Conotrachelus dimidiatus (Coleoptera: Curculionidae) in Guava Trees - Felipe Tafoya; Catarino Perales-Segovia; Ernesto Gonzalez-Gaona; Humberta Gloria Calyecac-Cortero (Psyche: A Journal of Entomology)
We evaluated the damage patterns produced by females of the guava weevil Conotrachelus dimidiatus Champion, 1904 (Coleoptera: Curculionidae), according to the position of the damaged fruit in guava trees Psidium guajava L. in Calvillo, Aguascalientes, Mexico. The trees were subdivided in eight zones, and during one year the level of fruit lesions due to oviposition was registered. Results showed a higher level of damage in the upper and external zone of the trees (P≤.05). We found no significant differences in damage between the four cardinal points (P≥.05). During the year, the level of damage was recorded and was higher in the months of August and September (P≤.05) associated with rainfall (0.86, P=.06) and increase in temperature (0.84, P=.03). The most susceptible fruits were in the size range of 2.1–4.0 cm (polar diameter). The information from this study will be used to design and establish effective control strategies for the guava weevil, taking into account location of the most susceptible fruits, seasonality of the pest, and the abiotic factors.